THE MEDIATING ROLE OF TEACHER COLLABORATION IN THE RELATIONSHIP BETWEEN PLCS AND TEACHING EFFECTIVENESS IN THE MALDIVES - Al-Amin Mydin,; Mohamed Nasir, (Journal of Islamic, Social, Economics and Development, 2023)
This study thoroughly investigated the mediating role of teacher collaboration within Professional Learning Communities (PLCs) in Maldivian schools. Utilising the Teacher Collaboration Assessment Scale (TCAS) developed by Woodland, Lee, and Randall (2012), key aspects of teacher collaboration, dialogue, decision-making, action, and evaluation (DDAE), were explored. Surveys involving 390 teachers across four provinces provided data analysed using SPSS IBM version 23 and PLS-SEM 3.0. The research unveiled a significant and transformative connection, emphasising the pivotal role of collaborative teacher practices within PLCs in enhancing teaching effectiveness. These findings hold significant implications for educational stakeholders, underscoring the importance of nurturing robust teacher collaboration mechanisms. As Maldivian schools strive for educational excellence, recognising and fostering the mediating influence of teacher collaboration within PLCs emerges as a strategic imperative, ensuring a progressive and empowered educational landscape for educators and students.